Comparisons of retinal vessel diameter and glaucomatous parameters between both eyes of subjects with clinically unilateral pseudoexfoliation syndrome - Takai, Yasuyuki (PLoS One, 2017)
PURPOSE: Pseudoexfoliation syndrome (PEX), the most common identifiable cause of open-angle glaucoma, might affect the retinal hemodynamics. To test this, we compared retinal vessel diameter and glaucoma-related parameters between eyes with pseudoexfoliation material (PE+) and fellow unaffected (PE-) eyes of patients with clinically unilateral PEX. METHODS: The medical records of 30 consecutive Japanese subjects were reviewed retrospectively. The retinal vessel diameters were measured and expressed as the central retinal arteriolar equivalent (CRAE) and central retinal venular equivalent (CRVE) using standardized software. During the chart review, we recorded glaucoma-related parameters including intraocular pressure (IOP), visual field mean deviation (MD) value, planimetrically measured vertical cup-to-disc (C/D) ratio, circumpapillary retinal nerve fiber layer thickness (cpRNFLT) and macular inner retinal thickness (mIRT) measured by spectral-domain optical coherence tomography, anterior chamber flare (ACF), corneal endothelial cell density (CECD), and number of antiglaucoma medications. RESULTS: Compared with PE- eyes, the CRAE, CRVE, MD, cpRNFLT and mIRT, and CECD were significantly lower in PE+ eyes; the IOP, vertical C/D ratio, number of antiglaucoma medications, and ACF were significantly higher in PE+ eyes (P<0.0001 for all comparisons). The CRAE, cpRNFLT, and MD were correlated positively with each other (ρ = 0.456–0.499, P<0.0001–0.0002) and negatively with the IOP (ρ = -0.562- —0.432, P<0.0001–0.0006). The vertical C/D ratio was correlated positively with the IOP (ρ = 0.483, P<0.0001) and negatively with the CRAE, cpRNFLT, and MD (ρ = -0.745–-0.479, P<0.0001–0.0001). CONCLUSIONS: Deposition of PE can cause retinal vessel narrowing in arterioles and venules. The roles and mechanisms of retinal vessel narrowing in glaucoma pathogenesis need clarification.